Modeling Fuzzy B-spline Interpolation Series using α-cut operation for spatial earth surface problem. Issue 1 (July 2021) - Abu Bakar, N A; Yusoff, B; Wahab, A F; Mamat, M
Abstract: In this paper, the series of α-cut is also known as the α-cut operation used to construct a new model of surface called Fuzzy B-spline Interpolation Series surface. The surface is called Fuzzy B-spline Interpolation Series because of the various values of α chosen in the fuzzification method. Then, the operation is combined into a B-spline surface model. This new proposed model will be used to solve spatial earth surface problems in every collected data points. The spatial earth data have values in latitude, longitude and altitude. All these values are considered as uncertainty data because of the satellite's measurement errors. Finally, constructed surfaces' results will be compared between raw data's surface and Fuzzy B-spline Interpolation Series surface.